A Composite Tissue Flap for Double-Eyelid Blepharoplasty in Asian Patients: A Retrospective Study. Issue 7 (24th October 2021) - Fu, Xiujun; Zhou, Xianyu; Sun, Di; Gu, Chuan
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Double-eyelid blepharoplasty, the procedure to create supratarsal crease, has been one of the most popular cosmetic operations in Asia for many years. This study aimed to assess the effectiveness and safety of a surgical procedure using a composite tissue flap for double-eyelid blepharoplasty. A surgical technique was introduced and patients having blepharoplasty with this technique from January 2017 to August 2019 were retrospectively studied. In this technique, a composite tissue flap consisted of the posterior septum and levator aponeurosis was formed and fixed with orbicularis oculi muscle and tarsus. The cosmetic outcomes, patient satisfaction, and complications from the documented medical records were analyzed. Eighty female and 1 male patients had blepharoplasty with the proposed technique and were followed up from 6 months to 42 months. Six patients were found to have mild blepharoptosis. As for cosmetic outcomes, 71patients were graded as good, 7 patients were graded as fair, and only 1 patient was graded as poor. Those patients who were not graded as good had visible scarring, shallow eyelid crease, or asymmetry. The overall patient satisfaction was as high as 95.1%. Mild hematoma formation occurred in 3 patients and no infection or blepharoptosis was observed. One patient complained of asymmetry and 2 patients complained of unilateral crease fading as the complications. The technique is effective to develop durable and natural-looking double eyelids with minimal complications. It could also be an option for mild ptotic patients who ask for double-eyelid blepharoplasty.